Microbiological Profile and Antibiotic Resistance Pattern in Acuteexacerbations of COPD: A Study from Northern India - Anusha, Pilli; Kaur, Kamaldeep; Lakshmi, Nunsavathu (Journal of College of Medical Sciences-Nepal, 2024)
Background Chronic Obstructive Pulmonary Disorder (COPD) is a major cause of morbidity and one of the principal causes of death worldwide. The objective of this study is to identify the bacterial etiological agents in patients with acute exacerbations of COPDs by sputum culture and their antibiogram. Methods This is a prospective study comprising 100 diagnosed patients of COPD taken as GOLD Grade 4 who were admitted in the Department of Pulmonary Medicine, TB and Chest Hospital which comes under King George Hospital, Visakhapatnam. Results Out of 100 patients, 83 were males of which 87% were smokers. The most common organisms isolated were Gram negative bacilli in 51 patients and only 26 were Gram positive cocci. The most common Gram-negative isolate was Klebsiella pneumoniae 27 cases followed by Pseudomonas aeruginosa in 19 cases. The most common Gram-positive isolate was Streptococcus pneumoniae in 16 cases followed by Streptococcus pyogenes in 6 cases and Staphylococcus aureus in 2 cases. Conclusions Frequent exacerbations appear to be associated with worsening healthoutcomes and effort should focus on prompt and effective treatment of eachepisode. Bacterial pathogens, mostly Gram negative bacilli are found to be the chief etiological agents in AECOPD. Antibiotic therapy should be initiated early depending on the culture. Susceptibility patterns of that particular region should be determined to prevent antibiotic resistance and to decrease health costs.